Bear necessity : [large type] / a novel - Gould-Bourn, James (Thorndike Press large print core, 2020)
"Danny's life is falling apart. He's become a single father to eleven-year-old Will--who hasn't spoken since the death of his mother in a car crash a year earlier--and Danny has just been fired from his construction job. To make matters worse, he's behind on the rent and his nasty landlord is threatening to break his legs if he doesn't pay soon. Danny needs money, and fast. After observing local street performers in a nearby park, Danny spends his last few dollars on a tattered panda costume, impulsively deciding to become a dancing bear"--